2019
DOI: 10.1001/jamacardio.2018.4472
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physician Variation in Use of Manual Aspiration Thrombectomy With Outcomes Following Primary Percutaneous Coronary Intervention for ST-Elevation Myocardial Infarction

Abstract: IMPORTANCE Following negative randomized clinical trials, US guidelines downgraded support for routine manual aspiration thrombectomy (AT) during primary percutaneous coronary intervention (pPCI) for ST-segment elevation myocardial infarction (STEMI). However, some PCI operators continue to endorse a clinical benefit with AT use despite the lack of supportive data. OBJECTIVE To examine temporal trends and comparative outcomes of AT use during pPCI for STEMI. DESIGN, SETTING, AND PARTICIPANTS Retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Review of the United States National Cardiovascular Data Registry (NCDR) CathPCI Registry by Secemsky et al shows that the uptake of AT has appropriately been low in the recent past. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Review of the United States National Cardiovascular Data Registry (NCDR) CathPCI Registry by Secemsky et al shows that the uptake of AT has appropriately been low in the recent past. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Balancing properties were assessed using standardized differences and balance plots. As previously suggested, 12 a standardized difference of ≥0.1 was considered a meaningful imbalance in the covariates. Standard errors of the propensity score matching analysis were not adjusted for clustering by hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…MT use has decreased progressively since 2016 despite the progressive increase in P-PCI. 4,5,28 This is not surprising but it could also underscore that MT is being avoided in excess. For example, the meta-analysis performed by the Thrombectomy Trialists Collaboration reported that there were no significant differences in recurrent myocardial infarction, stent thrombosis, heart failure, or target vessel revascularization in patients treated with MT but patients with high thrombus burden MT was associated with fewer cardiovascular deaths (HR: 0.80; 95% CI 0.65-0.98; p = .03).…”
Section: Ddta Score and Mt Outcomesmentioning
confidence: 95%
“…MT use has decreased progressively since 2016 despite the progressive increase in P‐PCI 4,5,28 . This is not surprising but it could also underscore that MT is being avoided in excess.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation